The Influence of Multiple Representation-Based Online Lectures Using Geogebra on Understanding of Students' Thermodynamics Concepts During the Covid-19 Pendemic Period - Tri Isti Hartini; Martin Martin (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to determine the effect of online lectures Via Zoom in thermodynamics courses based on multiple representations using Geogebra on students' conceptual understanding in the midst of physical standing conditions (Pendemic Covid-19). The research method used is preexperimental design (nondesigns). The research phase includes preliminary studies, including field surveys and literature studies. The stage of designing and reviewing test instruments based on Multiple Representations (MR). The MR-based test instrument was then used as an instrument to perform the pretest and posttest. From the analysis of research data, it was found that the average value of students' conceptual understanding before being given treatment was 42, while the average value of student learning outcomes after being given treatment was 77. After the calculations were carried out for hypothesis testing, it was obtained that t count was 4.293 and t table was 1.318, because t arithmetic t table that is 4.293 1.318 then H 0 is rejected. Thus H1 is accepted which states that there is an effect of online lectures via zoom in the thermodynamics subject based on multiple representations using Geogebra on students' conceptual abilities in the midst of the covid -19 pandemic